2005
DOI: 10.4049/jimmunol.175.2.1030
|View full text |Cite
|
Sign up to set email alerts
|

X Box-Like Sequences in the MHC Class II Region Maintain Regulatory Function

Abstract: Sequences homologous to the canonical MHC class II (MHC-II) gene X box regulatory elements were identified within the HLA-DR subregion of the human MHC and termed X box-like (XL) sequences. Several XL box sequences were found to bind the MHC class II-specific transcription factors regulatory factor X and CIITA and were transcriptionally active. The histone code associated with the XL boxes and that of the HLA-DRA X box was determined. Using CIITA-positive and -negative B cell lines, CIITA-specific histone modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 44 publications
3
60
0
1
Order By: Relevance
“…Indeed, DNA looping and interactions of distal enhancers and locus control regions with promoters are important for the expression of MHC class II and ␤-globin genes (12,42), which are regulated at the level of transcriptional elongation. Moreover, one study found AIRE to be associated with such matrix attachment sites (44).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DNA looping and interactions of distal enhancers and locus control regions with promoters are important for the expression of MHC class II and ␤-globin genes (12,42), which are regulated at the level of transcriptional elongation. Moreover, one study found AIRE to be associated with such matrix attachment sites (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several XL sequences identified between HLA-DRA and HLA-DRB3 were found to be functionally important based on their ability to bind RFX and CIITA in vivo, and drive expression of a reporter gene. 60 Furthermore, Gomez et al (2005) 60 identified a structural interaction between an upstream XL-sequence and the HLA-DRA promoter using a chromatin-looping assay. Strikingly, it appears that certain XL sequences can contribute to a global increase in chromatin accessibility of the class II region and interact with proximal promoter regulatory sequences through DNA looping.…”
Section: Sxy-like Sequences and Mhc Class II Gene Regulationmentioning
confidence: 99%
“…ChIP Assays-ChIP assays were performed as described previously in Beresford and co-workers (15,25). Cells were cross-linked with formaldehyde for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These include the discovery of a potential locus control region located upstream of the MHC class II gene HLA-DRA (14). A recent search of the MHC-II locus identified additional X-Y box sequences that were not associated with functional MHC class II genes and were termed X-like (XL) boxes (15). The analysis of these sequences by chromatin immunoprecipitation (ChIP) indicated that some of them were functional as determined by their ability to bind RFX and CIITA, to drive the expression of a reporter gene, and to be associated with chromatin modifications that were similar to active MHC-II gene proximal promoter regions.…”
Section: The Human Major Histocompatibility Complex (Mhc)mentioning
confidence: 99%